Senior Public Management System in Chile (2004-2015): Analysis of its Effects on Institutional Performance Using Panel Data - Morales Casetti, Marjorie; Salas Portuguez, Rodrigo; Bustos Gutiérrez, Marco (Revista del CLAD Reforma y Democracia, 2022)
This article explores the effects of a reform inspired by New Public Management with the objective of analyzing whether the incorporation of technical criteria in the selection system for Senior Public Management (SADP) in Chile generates positive effects on institutional performance. Using quantitative, public and objective information from 72 Chilean public services, for the period 2004 to 2015, five statistical models are estimated using data panel. The explanatory variable used is the length of tenure of the SAPD appointee, which accounts for accumulated experience. Five outcome variables related to institutional performance are used, one for each model: productivity, efficiency, annual budget execution, budget execution at the third quarter and compliance with performance indicators. The results show that there are only significant effects of the SADP on compliance with the performance indicators, which indicates that the political-technical system for the selection of top management in Chile has not had the expected results since its creation. One of the possible causes is the low time of permanence in the position, less than three years, which is not enough to achieve the required learning to contribute to the improvement of management and service provision.